(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SUMMARY: 1. Introduction to the role of UNESCO in defining, respecting and implementing Human Rights and Fundamental Freedoms: a general analysis - 2. The right to participate freely in cultural life: the specific UNESCO’s involvement in the field of religious rights - 3. IHL Dimension linked to UNESCO’s Legislative Powers to Protect the Cultural Heritage in the Event of Armed Conflict or Occupation - 4. UNESCO’s Actions to Preserve the Cultural Heritage in Syria and Iraq: A comparative framework - 5. The Legal Status of Jerusalem and the management of the Holy Places: Jerusalem in a Nutshell - 6. UNESCO’s past interventions in Jerusalem: a legal basis for future interventions - 7. The Mughrabi Gate Ascent - 8. The 2008 Action Plan for the Safeguarding of the Cultural Heritage of the Old City of Jerusalem - 9. UNESCO, Resolution 200 EX/PX/DR.25.2:“Occupied Palestine” - 10. Conclusions. ABSTRACT: The current dissertation is mainly going to analyse the original contribution of UNESCO to the development of the concept of cultural rights through the proclamation and elaboration of normative instruments and strategies concerning the right to the protection of and access to the cultural (religious) heritage in contested areas. Since 1967, UNESCO has increasingly played a dominant role in the Old city of Jerusalem: it exercised its power in the field of the preservation of cultural heritage in a contested area, not only through practical plans, but also through legislative instruments and Resolutions. A peculiar political contest is still challenging the full exercise of its powers and the applicability of the main human rights treaty dealing with the preservation of cultural heritage in a contest of competing sovereignty. The essay, drawing on UNESCO’s past restoration experiences in ancient (Aleppo, 1992) and post-conflict (Iraq, 2003) areas, focuses on the conciliation role that the Agency may potentially play in the Israeli-Palestinian conflict.